Dysregulation of the CD4+ T cells lineage differentiation in dyslipidemic patients and impact of lipoprotein-apheresis treatment: A case study. (November 2017) - Papin, J.; Brennand, A.; Arbore, G.; Hohenstein, B.; Kamvissi, V.; Kemper, C.; Bornstein, S.R.
Abstract: Background and aim: Lipoprotein-apheresis (LA) is a therapeutic approach used against severe forms of dyslipidemia in patients who are non-responders or intolerant to pharmacological treatments. However, little is known about the potential pleiotropic effects of LA, particularly regarding the immune system and its regulation. Thus, in an attempt to analyse the potential effects of dyslipidemia and LA on the regulation of CD4 + T cells activation and lineage differentiation, we compared the CD4 + T cells cytokines secretion profiles of dyslipidemic patients before and after LA with the profiles observed in healthy donors. Methods: CD4 + T cells were isolated from 5 LA patients and 5 healthy donors and activated with anti-CD3 or anti-CD3 + anti-CD46 antibodies. The supernatants were collected after 36 h incubation and levels of secreted cytokines analysed by flow cytometry. Results: Our results revealed a deep remodelling of CD4 + T cells cytokines secretion patterns in dyslipidemic patients compared to healthy donors, as reflected by a 15 times higher IFN-γ secretion rate after CD3 + CD46 co-activation in dyslipidemic patients after LA compared to healthy subjects and 8 times higher after CD3 activation alone ( p  = 0.0187 and p  = 0.0118 respectively). Moreover, we demonstrated that LA itself also modifies the phenotype and activation pattern of CD4 + T-cells in dyslipidemic patients. Conclusion: These observations could be of fundamental importance in the improvement of LA columns/systems engineering and in developing new therapeutic approaches regarding dyslipidemia and associated pathologies such as atherosclerosis and type 2 diabetes.